1996
DOI: 10.1002/eji.1830260202
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of a model antigen by Au(III) leads to T cell sensitization to cryptic peptides

Abstract: Certain metal ions are known to be potent sensitizers, but the self proteins modified by metal ions and the self peptides recognized by 'metal-specific' T cells are unknown. In humans and mice treatment with gold anti-rheumatic drugs, containing Au(I), may lead to allergic and autoimmune side effects. Human and murine T cells do not react to Au(I), however, but to the reactive metabolite Au(III). Here we show that alteration by Au(III) of a model antigen, bovine ribonuclease (RNase)A, results in T cell sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
66
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 40 publications
4
66
0
Order By: Relevance
“…As mercury-protein interaction has been shown to alter protease sensitivity (16), it is possible that mercury modification of fibrillarin may influence Ag processing, leading to the production of cryptic T cell determinants. Abnormal Ag processing of metal-modified protein is supported by recent studies that have identified cryptic peptides that stimulate IL-2 production by T cell hybridomas obtained from mice immunized with bovine RNase A complexed to gold (17,18). The cryptic nature of these determinants has been suggested by studies showing that T cell hybridomas from mice immunized with bovine RNase alone do not respond to the same peptides (17,18).…”
mentioning
confidence: 98%
“…As mercury-protein interaction has been shown to alter protease sensitivity (16), it is possible that mercury modification of fibrillarin may influence Ag processing, leading to the production of cryptic T cell determinants. Abnormal Ag processing of metal-modified protein is supported by recent studies that have identified cryptic peptides that stimulate IL-2 production by T cell hybridomas obtained from mice immunized with bovine RNase A complexed to gold (17,18). The cryptic nature of these determinants has been suggested by studies showing that T cell hybridomas from mice immunized with bovine RNase alone do not respond to the same peptides (17,18).…”
mentioning
confidence: 98%
“…with Au(III) results in T cell sensitization in mice to so-called 'cryptic peprides'j derived from this protein while T cells from mice injected with RNase alone are sensitized only to a common, the immunodominant, peptide derived from RNase (38). The scission and presentation of cryptic peptides may arise from gold(III)-induced oxidation of methionine residues and/or gold(III)-induced conformational changes in the antigenic protein leading to a different intracellular processing of the protein and therefore to the formation of different antigenic peptides.…”
Section: Interaction Of Gold(iii) With Peptidesmentioning
confidence: 99%
“…The scission and presentation of cryptic peptides may arise from gold(III)-induced oxidation of methionine residues and/or gold(III)-induced conformational changes in the antigenic protein leading to a different intracellular processing of the protein and therefore to the formation of different antigenic peptides. The novel aspect of these data is that the metal is not involved in the recognition process between MHC class II protein, peptide and T cell, but affects the prior processing step of a protein altered by the effect of the metal (gold) (38), (Figure 2b It has recently been suggested that gold(III) produced from gold (I) drugs might be involved in the toxic sideeffects encountered in chrysotherapy. The chronic treatment of mice with gold(I) drugs results in the production ofT cells that are stimulated not by gold(I) but by gold(III) (36) and patients with gold-induced dermatitis show significant lymphocyte proliferation in response to gold(III) but not to gold (I) [37].…”
Section: Interaction Of Gold(iii) With Peptidesmentioning
confidence: 99%
See 2 more Smart Citations